DAMPAK PEMANFAATAN MEDIA AUDIO VISUAL DAN MOTIVASI TERHADAP HASIL BELAJAR TARUNA DIPLOMA III PRODI MTU 3, PLLU 60 B, PKPPK 10, PA 11, TMB 6 DAN TLB 24 PADA MATA KULIAH PAI DI SEKOLAH TINGGI PENERBANGAN INDONESIA - Alwazir Abdusshomad (Langit Biru: Jurnal Ilmiah Aviasi, 2020)
The research purpose is to know the using of audiovisual media and motivation toward diploma 3 cadets’ achievement of MTU 3, PLLU 60 B, PKPPK, PA 11, AND TLB 24 in PAI subject at STPI. There are six questions research such as 1) how the using of audiovisual media is, 2) how the cadets’ motivation is, 3) how the cadets’ achievement is, 4) are there any impacts of the audiovisual utilization toward the cadets’ achievement in the PAI subject, 5) are there any impacts of the cadets’ motivation toward the cadets’ achievement, and 6) are there any impacts of the audiovisual utilization and motivation toward the cadets’ achievement in the PAI subject. This research is quantitative method. To collect the data, the researcher used questionnaire and documentation. 105 cadets became the research population and 53 cadets as the sample. The research result showed that 1) the using of audiovisual media was high categorization, 64.15%; 2) cadets’ motivation was high categorization, 73.58%; 3) cadets’ achievement was high categorization, 67.92%; 4) there were no impact in using audiovisual media toward the cadets’ achievement in PAI subject. The result showed rh < rt (0.256 rt (0.499 > 0.361); 6) there were any impact of using audiovisual media and motivation toward the cadets’ achievement in PAI subject. The result showed rh > rt (0.532 > 0.361). Using the F-test 5% significance level, the researcher obtained 10.071 as Fh and 3.18 as Ft. So, it can be concluded that Fh > Ft (10.071 > 3.18). It meant that linear regression was significant